Valid trust declarations over property not owned by the settlor or over unascertainable property. Issue 2 (13th January 2020) - Wilde, David
Abstract: It seems to be widely believed that settlors can never make valid declarations of trust over property that, at the time of the declaration, they do not own; or which is unascertainable then. It is argued that this is a misconception: arising from a failure to distinguish between (1) rules applicable to self-declarations of trust and (2) rules applicable to declarations of trust to be constituted by vesting title to property in others as trustees.